Contemporary Trends of Digitalisation of Management Processes in Higher Education: Data Analytics, Cloud Technologies and Artificial Intelligence - Viacheslav, Osadchyi (Educological discourse, 2024)
The continuous development, improvement and diversification of digital technologies cause the issue of rethinking their use in education, in particular, in the context of digitalisation of management processes at higher education institutions. It is important to understand the current state and trends of digital technologies, which become the basis for digitalisation of management processes in higher education. For this purpose, the article has analysed Ukrainian publications in the Google Scholar search engine to identify scientific works dealing with the digitalisation of management processes in higher education, using Scopus AI, the tool based on artificial intelligence, to obtain a conceptual map of digitalisation technologies of management processes in education, studied publications in the Scopus international scientometric database to determine the significance of digital technologies described in these publications. The article analyses digital technologies currently used for management tasks in higher education, namely: data analytics, cloud technologies, and artificial intelligence technologies. The main advantages of the digitalisation of management processes in higher education are highlighted: effective administration, improvement of the decision-making process, improvement of the provision of educational services, improvement of teaching. Challenges and difficulties accompanied by digitalisation of management processes in higher education are presented: insufficient financing of higher education; lack of understanding of the educational process by the participants (from students to managers) regarding processes taking place in the modern digital society, as well as emerging or changing technologies; the need for competent management and teaching staff, a high level of digitalisation of society at the national level, orientation of educational process participants in a large number of digital technologies. As a result of the study, the current trends in digitalisation of management processes in higher education are summarised (continuation of the process of introducing digital technologies into the educational process in general and management processes in higher education in particular; integration of these digital technologies into learning management systems; introduction of updated digital technologies into the teaching process; improvement of education through digital transformation of management processes.